PENGARUH GOOD CORPORATE GOVERNANCE (GCG), LEVERAGE, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN DENGAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL MEDIASI - Sutopo, Dian; Rokhmawati, Andewi; Andreas, Andreas (Jurnal Tepak Manajemen Bisnis, 2018)
Government regulations require companies to implement CorporateSocial Responsibility (CSR). CSR is expected to increase company value.However, in reality the companys value measured using TobinsQ decreases. Sothe objective of this research is to analyze the effect of Good CorporateGovernance (GCG), leverage, and profitability to firm value with CSR as amediation variable.The population of this research is all public companies listed on the BursaEfek Indonesia (BEI) in 2015 as many as 525 companies. The sample of thisresearch is 100 companies with purposive sampling technique. Criteria: is apublic listed company listed on IDX and has the largest market capitalizationranking in 2015 based on Institute for Corporate Directorship (IICD) calculation.Testing is done by using mediating regression analysis with sobel test.The results showed that the variables that have significant effect on CSRare GCG, while the leverage and profitability variables have no effect on CSR.Variables that significantly effect to the firm value is GCG and profitability,while the leverage and CSR variables have no effect to the firm value. The CSRvariable also does not mediate the effect of GCG, leverage, and profitability onfirm value. The implications of this research for companies: companies that havenot done CSR in a suistanable and still philanthropic can not see the impact ofCSR significantly through firm value. Increasing the value of the companythrough CSR activities will be felt by the company in the long term, for theimplementation of CSR should be done in a suistanable and strategic activities ofthe company.